Influence of IP Collaboration and FOMO on Impulse Buying Behavior - Hisbulloh Edgaritoh; Ratih Amelia; Riska Dhenabayu; Muhammad Fachmi (STIE AMKOP, 2026)
The rapid growth of digital technology and social media has transformed the way Millennials and Gen Z make purchasing decisions. This study examines the influence of Intellectual Property (IP) collaboration strategy and Fear of Missing Out (FOMO) on impulse buying behavior in the FamilyMart x Demon Slayer collaboration in Surabaya. Based on the Stimulus-Organism-Response (SOR) framework, brand collaboration acts as a marketing stimulus that enhances attractiveness, uniqueness, and emotional attachment, while FOMO reflects anxiety and urgency to avoid missing rewarding experiences. Impulse buying is defined as spontaneous and emotionally driven purchasing behavior. A quantitative survey method with purposive sampling of 120 respondents was used. Data were analyzed through multiple linear regression. The results show that both IP collaboration strategy and FOMO have positive and significant effects on impulse buying behavior, both partially and simultaneously. This study contributes to understanding how emotional marketing and psychological triggers drive consumer behavior in pop culture-based retail collaborations.